Chronic endurance exercise induces quadriceps nitrosative stress in patients with severe COPD. Issue 1 (3rd October 2008) - Barreiro, E; Rabinovich, R; Marin-Corral, J; Barberà, J A; Gea, J; Roca, J
Abstract : Background: Although exercise training has beneficial effects on skeletal muscle bioenergetics and exercise performance in patients with severe chronic obstructive pulmonary disease (COPD), it may also be associated with increased quadriceps oxidative and nitrosative stress. The aim of this study was to explore quadriceps oxidative and nitrosative stress in patients with severe COPD, both before and after a 3 week endurance exercise programme, and to identify the nature of the oxidatively modified proteins. Methods: Reactive carbonyls, hydroxynonenal–protein adducts, antioxidant enzymes, nitric oxide synthase (NOS) and 3-nitrotyrosine levels were determined in the quadriceps (pre- and post-exercise) of 15 patients with severe COPD and seven healthy controls using immunoblotting (one- and two-dimensional electrophoresis), activity assays and mass spectrometry. Results: At baseline, muscle levels of reactive carbonyls, which were negatively associated with muscle strength and exercise tolerance, were significantly higher in patients than in controls. Moreover, baseline hydroxynonenal–protein adducts, superoxide dismutase activity, inducible NOS and 3-nitrotyrosine immunoreactivity levels were also significantly increased in the quadriceps of patients compared with controls. In patients, chronic exercise induced a significant rise in inducible NOS levels and a fourfold increase in protein nitration. Chronic endurance exercise induced tyrosine nitration of muscle enolase 3β, aldolase A, triosephosphate isomerase, creatine kinase, carbonic anhydrase III, myoglobin and uracil DNA glycosylase in the quadriceps of patients, while contractile protein alpha-1 actin was nitrated only in patients exhibiting muscle loss (post hoc analysis). Superoxide dismutase activity increased after the exercise programme only in controls. Conclusions: In severe COPD, chronic endurance exercise induces increased tyrosine nitration of quadriceps proteins involved in glycolysis, energy distribution, carbon dioxide hydration, muscle oxygen transfer, DNA repair and contractile function in patients exhibiting systemic effects of the disease.